'It's Mental Health, Not Mental Police': A Human Rights Approach to Mental Health Triage and Section 136 of the Mental Health Act 1983. (29th August 2017) - Morgan, Matthew; Paterson, Craig
Abstract: A human rights approach to the policing of mental ill-health raises fundamental questions about the vulnerability of people in the care of the police, the appropriateness of police interventions, and how societies define and delineate the role and function of the police and health sectors. It is the challenge of understanding and interpreting the police–health nexus and its associated points of intervention that this article addresses. The article uses a human rights framework to explore the challenges that emerge when policing mental ill-health through the use of Section 136 of the Mental Health Act 1983 and recent experimental use of mental health triage in England and Wales. The article explores the potential of triage to alleviate some of the human rights concerns associate with the use of Section 136 through interviews with police officers involved with the triage pilots. The final discussion situates experiments with mental health triage against a backcloth of mental health's increasingly prominent position on the global public policy agenda. The article concludes with call for a reassessment and realignment of thinking about the police–health nexus that aligns with the United Nations' sustainable development goals for 2030.